2008
DOI: 10.1308/003588408x241999
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Training is No Longer than Other Surgical Specialties

Abstract: INTRODUCTION There is a perception that the training pathway for oral and maxillofacial surgery (OMFS) is unduly long and arduous, as consultant oral and maxillofacial surgeons must be doubly qualified (that is, hold degrees in medicine and dentistry) and be holders of two higher fellowships. MATERIALS AND METHODS We reviewed the data regarding the average age of National Training Number (NTN) holders and GMC data on the year of first registration and the year of entry onto a specialist surgical list for all 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Interestingly, previous data have found that the age at which OMFS trainees achieve their consultant posts is not greater than other surgical specialties . Despite this, trainees maintain their reservations regarding training time.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, previous data have found that the age at which OMFS trainees achieve their consultant posts is not greater than other surgical specialties . Despite this, trainees maintain their reservations regarding training time.…”
Section: Discussionmentioning
confidence: 92%
“…A model implemented in the USA where, while 4-year residency programs in OMS grant a certificate of specialty, 6 years residency programs grant the specialty certificate as well as a medical degree (additional 2 years for acquiring medical degree), this may also be tailored to Turkish education system. The British system where shortened medical degrees, which take 3-4 years are available for holders of a dental degree in the UK may also be the other alternative [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been noted that training in OMFS is no longer than other surgical specialties. 3 Yet, Modernising Medical Careers has reduced the time spent in basic surgical training from an average of 30 months to 12 months. 4 Indeed much of the curricula relating to postgraduate dental training will have been covered in part during the postgraduate foundation, general surgical, and oral and maxillofacial surgery training.…”
Section: Discussionmentioning
confidence: 99%